AB0567 Joint Involvement in Patients Affected by Systemic Lupus Erythematosus: Application of The Swollen to Tender Joint Count Ratio. (9th June 2015) - Cipriano, E.; Ceccarelli, F.; Massaro, L.; Spinelli, F.R.; Miranda, F.; Truglia, S.; Pendolino, M.; Leccese, I.; Alessandri, C.; Perricone, C.; Valesini, G.; Conti, F.
Abstract : Background: Joint involvement is one of the most common manifestations in patients with Systemic Lupus Erythematosus (SLE). The SLE Disease Activity Index 2000 (SLEDAI-2K) identifies the presence of joint involvement only in case of ≥2 joints with pain and signs of inflammation. It is therefore clear that this stringent definition could fail to catch the great variety of expressions of the joint involvement. Recently, it has been proposed the application of the Disease Activity Score 28 (DAS28) in a cohort of SLE patients with ongoing joint involvement, demonstrating a moderate/high disease activity according to DAS28 in 50% of SLE patients with a joint involvement not defined by SLEDAI-2K (1). Kristensen et al. proposed a new index based on the ratio of the swollen and tender joints on 28-joint count (swollen to tender joint count ratio - STR), in order to evaluate the response to biological treatment in Rheumatoid Arthritis patients (2). Objectives: We aimed at assessing articular involvement in a SLE cohort by using the STR. Methods: One hundred SLE patients (F/M 95/5, mean ± SD age 46.3±10.6 years, mean ± SD disease duration 147.1±103.8 months), complaining of joint symptoms (at least 1 tender joint) were enrolled. All patients underwent a complete visit, including patient's assessment by a visual analogue scale (Global health, GH; 0-100 mm). Disease activity was assessed by SLEDAI-2K. We assessed the swollen and tender joint count (0-28). The STR was calculated as the ratio of the swollen joints and tender joints count (2). According with the STR values, SLE patients have been grouped into three categories of disease activity: low (STR <0.5), moderate (≤0.5 STR ≤1.0), high (STR >1.0) (2). The DAS28-ESR was also calculated. Results: The evaluation of the tender and swollen joints count identified a median of 4 (IQR 7) and 1 (IQR 2.5), respectively. The median STR value was 0.03 (IQR 0.6; mean ± SD 0.6±1.7). According with the STR values, 70 patients had low disease activity, 23 moderate and 7 high. The DAS28-ESR median was 4.1 (IQR 1.96). A positive correlation between the STR and DAS28-ESR (P=0.001; r=0.33) and between STR and ESR (P=0.01; r=0.25) was observed. We further evaluated the 66 patients without joint involvement defined by SLEDAI-2K (Group 1). All these patients had low (91%) or moderate (9%) STR. The 34 patients with joint involvement identified by the SLEDAI-2K (Group 2) had a low STR in 29.4%, moderate in 50.0% and severe in 20.6% of cases. Conclusions: In the present study, we used for the first time the STR index to evaluate joint involvement in SLE patients. Our results demonstrated that STR is more sensitive than SLEDAI-2K in capturing joint involvement, possibly allowing a better assessment of this frequent manifestation. References: Ceccarelli F, et al. The role of disease activity score 28 in the evaluation of articular involvement in systemic lupus erythematosus. ScientificWorldJournal. 2014;2014:236842. Kristensen LE, et al. Is swollen to tender joint count ratio a new useful clinical marker for biologic drug response in rheumatoid arthritis? Results from a Swedish cohort. Arthritis Care Res (Hoboken). 2014;66:173-9. Disclosure of Interest: None declared